A Vicious Tenacity: The Efficiency Strategy Confronted With the Rebound Effect - Arrobbio, Osman; Padovan, Dario (Frontiers in Energy Research, 2018)
Studies of the phenomena known as the ‘rebound effect’, ‘backfire’ and the ‘Jevons Paradox’ have cast doubt on the effectiveness, in terms of reduction of energy use, of measures based on efficiency gains. Some of them have shown that efficiency improvements are less effective than expected, others have lent strength to the hypothesis that efficiency improvements are counterproductive in the long run. The difference between the two groups is thus all but negligible. Moreover, it is of considerable pragmatic significance as it may undermine the foundations of solid expectations that had led to ongoing systems and repertoires of action. In this paper we provide a model about the hypothesis that the expectations related to the effects that efficiency gains have on energy and resource consumption may exacerbate the rebound effect and that they prevent alternative strategies, that may turn out to be more effective in reducing energy and resource use, to be enacted. In the concluding paragraph, we propose possibilities for further hypothesis and empirical research that could lead to the refinement of the model.